What We Know About Team Dynamics for Long-Distance Space Missions: A Systematic Review of Analog Research - Bell, Suzanne T.; Brown, Shanique G.; Mitchell, Tyree (Frontiers in Psychology, 2019)
Background: To anticipate the dynamics of future long-distance space exploration mission (LDSEM) teams, research is conducted in analog environments (e.g., Antarctic expeditions, space chamber simulations), or environments that share key contextual features of LDSEM such as isolation and confinement. We conducted a systematic review of research conducted on teams in LDSEM-analog environments to identify which factors have been examined with quantitative research, and to summarize what the studies reveal about team dynamics in LDSEM-analog environments. Methods: We used a comprehensive search strategy to identify research on teams that lived and worked together. Data on team dynamics were extracted where possible, and sources were coded for key contextual features. The data did not lend themselves to traditional meta-analysis. We used two approaches to summarize the data: a weighted averages approach when the study reported enough data to calculate an effect size, and descriptive figures when data across studies were directly comparable. Results: Seventy-two sources met our inclusion criteria, yielding 253 effect sizes and 1,150 data points. Results from our weighted averages approach suggested that the team cohesion and performance relationship may be operating differently in isolated and confined environments than other teams that lived and worked together (e.g., military teams), and that, given the available data, we can say very little about the magnitude and direction of the relationship. Our descriptive figures revealed important trends: (a) team members in longer missions generally spent less social time together than shorter missions; (b) consistent team efficiency over time was typical, whereas decreased team efficiency over time was atypical; (c) by 40% of mission completion or 90 days, all teams reported at least one conflict, (d) commanders’ written communication with mission control decreased in length over time, and (e) team mood dynamics did not consistently support the third-quarter phenomenon. Conclusions: There are inherent limitations to our study, given the nature of the analog research (e.g., correlational studies, small sample size). Even so, our systematic review provides key insights into team dynamics in LDSEM-analog environments. We discuss the implications of our research for managing future space crews. Importantly, we also provide guidance for future research.